2023
DOI: 10.1155/2023/9713905
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Detection Models in Mexican Patients by Combining Machine Learning Algorithms and Feature Selection Techniques for Clinical and Paraclinical Attributes: A Comparative Evaluation

Abstract: The development of medical diagnostic models to support healthcare professionals has witnessed remarkable growth in recent years. Among the prevalent health conditions affecting the global population, diabetes stands out as a significant concern. In the domain of diabetes diagnosis, machine learning algorithms have been widely explored for generating disease detection models, leveraging diverse datasets primarily derived from clinical studies. The performance of these models heavily relies on the selection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…In addition to comparing our results with the findings of García et al [ 5 ], we also benchmarked our study against the work of Tanaka et al [ 11 ]. In comparison to Tanaka et al’s findings, our study demonstrated notable advancements in diabetes classification.…”
Section: Experiments and Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…In addition to comparing our results with the findings of García et al [ 5 ], we also benchmarked our study against the work of Tanaka et al [ 11 ]. In comparison to Tanaka et al’s findings, our study demonstrated notable advancements in diabetes classification.…”
Section: Experiments and Resultsmentioning
confidence: 82%
“…Table 4 presents the performance metrics of the Random Forests classification model, as recommended by García et al [ 5 ]. These metrics offer a comprehensive understanding of the effectiveness and reliability of the classifier when trained on the expanded dataset, thereby substantiating the potential advantages of utilizing GAN-generated synthetic data for improving the model’s predictive capabilities.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…K-Nearest neigbour (KNN) outperforms decision trees when used as a stacking combiner. A novel diabetes detection technique was presented by Domínguez et al [14] employing design of experiment, GA, and multi-layer perceptron (MLP). GA was  ISSN: 2252-8938 Int J Artif Intell, Vol.…”
Section: Review Of Literaturementioning
confidence: 99%